The Effect of Mother Tongue and Translation in Reading Comprehension - Alduweebi, Maryoumah Ateeyah; Al-rubshi, Samir (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
Reading comprehension heavily relies on the self-study of learners. This research aimed to determine the reasons behind the challenges learners face, specifically the effects of their mother tongue and the use of translation on comprehending written texts. The study sought to identify problems and gaps in reading comprehension strategies, to address the lack of effective translation techniques, and to provide learners with methods to minimize the influence of their mother tongue when learning a second language. A questionnaire was distributed to a sample of 52 EFL Libyan female students at Alasmarya Islamic University in the Faculty of Human Sciences for Girls, with ages ranging from 22 to 26 years old, who were in their seventh and eighth semesters. Additionally, interviews were conducted with four English teachers from the faculty. Data collected from the questionnaire and interviews were analyzed systematically. The findings indicated several reasons why students struggle to comprehend written texts effectively. These include: a lack of practice in reading strategies at home, neglecting the use of reading comprehension strategies, failing to take initiative in improving their reading skills, viewing learning English merely as a means to obtain certification and scores, not engaging deeply with the language, not becoming more academically inclined by using available websites and applications, and not considering their future careers as teachers.
Keywords: Reading Comprehension; Translation; Mother Tongue